Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1039/c8cp03593h
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the interfacial charge transfer behavior of hydrothermally synthesized ZnO nanostructures via complementary electrogravimetric methods

Abstract: The mechanism of species fluxes during the charge–discharge process in a nanostructured ZnO electrode was studied by a combined methodology of electrochemical quartz-crystal microbalance (EQCM) and ac-electrogravimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 40 publications
(48 reference statements)
1
12
0
Order By: Relevance
“…Figure 1B,C shows the morphologies of ZnO nanostructures, exhibiting vertically aligned individual nanorods with a length of ≈800 nm. These structures are distinct from the random orientation of the ZnO structures [31] and obtained by a two-step synthesis involving an electrochemically grown seed layer and a subsequent hydrothermal growth. A transparent ultrathin ERGO layer on the top of ZnO nanostructures is achieved by electrochemical reduction of a thin graphene oxide (GO) layer and clearly observed in Figure 1C.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Figure 1B,C shows the morphologies of ZnO nanostructures, exhibiting vertically aligned individual nanorods with a length of ≈800 nm. These structures are distinct from the random orientation of the ZnO structures [31] and obtained by a two-step synthesis involving an electrochemically grown seed layer and a subsequent hydrothermal growth. A transparent ultrathin ERGO layer on the top of ZnO nanostructures is achieved by electrochemical reduction of a thin graphene oxide (GO) layer and clearly observed in Figure 1C.…”
Section: Resultsmentioning
confidence: 93%
“…[28][29][30][31] Further information about these parameters is given in the Supporting Information. K i represents the transfer kinetics of each species while G i is the reciprocal of the transfer resistance (Rt i = 1/FG i ), exhibiting the ease or difficulty in the species transfer at the film/electrolyte interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 It is well known that in situ techniques, despite being powerful tools, display some technical limitations, such as the need for operation in a three-electrode setup; however, with some efforts, these results might be successfully translated to full-device performance. [16][17][18][19][20] In this context, the adsorption/ desorption of ions monitored by an electrochemical quartz crystal microbalance (EQCM) for a single electrode appears to be advantageous [21][22][23][24] and has already been applied to monitor capacitive [24][25][26][27][28][29] and faradaic charge storage processes. 30 Though, it is widely accepted that for highly porous activated carbon (AC) materials, the ion adsorption process is complex and could encounter several barriers preventing the full material capacity or capacitance from being exploited.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these developments in the use of EQCM based methods in the energy storage domain, here, a non-conventional complementary technique, the so-called ac-electrogravimetry has been proposed to unveil the mechanisms of the ionic exchange process [31][32][33]. It has been demonstrated that highly relevant and complementary information to the classical EQCM can be 5 obtained: (i) kinetics and identification of species transferred between the electrode and the electrolyte, (ii) separation of the different contributions related to the charged and non-charged species involved in the electrochemical processes, (iii) identification of species transferred in opposite flux directions provided that their kinetics are sufficiently different and (iv) variation of the relative concentrations of the species inside the examined material [34][35][36][37][38]. The originality of this method is its ability to discriminate between the interfacial transfer of cations, anions and solvent molecules involved (directly or indirectly) in the charge compensation process which is ultimately related to their charge storage performance.…”
Section: Introductionmentioning
confidence: 99%